Analysis of 153 cases of odontogenic cysts in a South Indian sample population: a retrospective study over a decade - Manickam Selvamani; Mandana Donoghue; Praveen Shivappa Basandi (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The purpose of this study was to determine the prevalence of odontogenic cysts and to identify their clinico-pathological features among patients by studying biopsy specimens obtained from the archives of the Department of Oral and Maxillofacial Pathology, College of Dental Sciences, Davangere, Karnataka, India, during the past 10 years. Data for the study were retrieved from the case records of patients fitting the histological classification of the World Health Organization (1992). Analyzed clinical variables included age, gender, anatomical location, and histological diagnosis. Of the 2275 biopsy reports analyzed, 194 cases (8.5%) were jaw cysts, including odontogenic (6.7%) and nonodontogenic cysts (0.25%). Odontogenic cysts included 69.3% radicular, 20.3% dentigerous, 5.2% keratinizing odontogenic, 3.3% residual, and 1.9% other cysts, such as lateral periodontal, botryoid odontogenic, and gingival cysts. The most frequent clinical manifestation was swelling, followed by a combination of pain and swelling. Age, gender, and location were related to the etiopathologic characteristics of the cyst type. A definitive diagnosis can be made on the basis of clinical, radiological, and histological findings, which makes a good interdepartmental relationship between the clinicians and pathologists essential. Knowledge of the biological and histological behavior of the odontogenic cysts is required for their early detection and treatment.